Analisis Protokol Keamanan Jaringan dalam Era Internet of Things (IoT) - Hidayatullah, Imam; Khairi, Muh Hafiz; Maulana, Irfan; Eka Putra, Fauzan Prasetyo (Infotek: Jurnal Informatika dan Teknologi, 2025)
This study explores the challenges and solutions related to information system security in the Internet of Things (IoT) era, focusing on smart homes and industrial settings. Using a qualitative approach through a comprehensive literature review, this research analyzes academic sources including journals, technical reports, and research publications. Findings show that cyber threats such as malware, ransomware, and denial of service (DoS) attacks significantly affect IoT system performance and reliability. Key issues include the absence of standardized security measures, limited device interoperability, and low user awareness. The study contributes by mapping critical security concerns in IoT ecosystems and offering strategic recommendations such as enhancing security protocols, developing data protection policies, and promoting user education. This research aims to support the development of secure, adaptive, and sustainable IoT systems in an increasingly connected digital world